Experimental analysis of microhardness changes of subsurface areas affected by WEDM - Mouralová, Kateřina; Michna, Štefan; Zahradníček, Radim; Bednář, Josef; Plichta, Tomáš; Fries, Jiří (Sage Publications, 2022)
The influence of the surface area by the impact of high temperatures after wire electric discharge machining (WEDM) is a known fact. However, the affected parameters also include a change in microhardness. In order to further investigate this statement, 5 different ferrous and non-ferrous materials were selected, from which three samples were always made with different settings of machine parameters (gap voltage, pulse on and off time, wire feed and discharge current). This examined not only the effect of the machining itself on the material but also whether the change in the microhardness of the material is affected by the setting of the machine parameters. In order to measure the microhardness of the subsurface layer, a metallographic preparation was made from each sample, which enabled accurate measurements always in the same area. Subsequent evaluation revealed that the microhardness may not be affected at all and everything depends only on the type of material being machined. The changes in microhardness affected by setting machine parameters are negligible.

The influence of the surface area by the impact of high temperatures after wire electric discharge machining (WEDM) is a known fact. However, the affected parameters also include a change in microhardness. In order to further investigate this statement, 5 different ferrous and non-ferrous materials were selected, from which three samples were always made with different settings of machine parameters (gap voltage, pulse on and off time, wire feed and discharge current). This examined not only the effect of the machining itself on the material but also whether the change in the microhardness of the material is affected by the setting of the machine parameters. In order to measure the microhardness of the subsurface layer, a metallographic preparation was made from each sample, which enabled accurate measurements always in the same area. Subsequent evaluation revealed that the microhardness may not be affected at all and everything depends only on the type of material being machined. The changes in microhardness affected by setting machine parameters are negligible.
Experimental analysis of microhardness changes of subsurface areas affected by WEDM
Keywords: WEDM; electrical discharge machining; microhardness; machining parameters; subsurface layer; WEDM; electrical discharge machining; microhardness; machining parameters; subsurface layer